2000
DOI: 10.1118/1.598892
|View full text |Cite
|
Sign up to set email alerts
|

On the beam quality specification of high‐energy photons for radiotherapy dosimetry

Abstract: An overview of common photon beam quality specifiers used in radiotherapy dosimetry introduces a reasoned discussion on the advantages and disadvantages of TPR20,10 and PDD(10)x. It is shown that some of the potential advantages of PDD(10)x are also present in other well known beam quality specifiers such as d80. However, all PDD-based beam quality indices, including PDD(10)x, are subject to electron contamination and their determination is affected by practical limitations. The proposed filtration of contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Last but not least, it must be noted that the slightly different relation between stopping‐power ratios and beam quality specifier between FFF and beams with flattening filter (WFF) should strictly be considered and taken into account in the relevant kQ,Q0 data. This has been included in the data tables of TRS‐483 for the reference dosimetry of both beam types.…”
Section: Physics Of Small‐field Dosimetrymentioning
confidence: 99%
“…Last but not least, it must be noted that the slightly different relation between stopping‐power ratios and beam quality specifier between FFF and beams with flattening filter (WFF) should strictly be considered and taken into account in the relevant kQ,Q0 data. This has been included in the data tables of TRS‐483 for the reference dosimetry of both beam types.…”
Section: Physics Of Small‐field Dosimetrymentioning
confidence: 99%
“…Plants adapt to osmotic stress mainly by reducing transpiration and accumulating osmotic adjustment substances (Chen M. et al, 2018). It has been reported that sorghum accumulated proline and soluble carbohydrates after NaCl treatment for 20 days (Heidari, 2009). The accumulation of these substances reduced the water potential of sorghum and maintained the waterabsorbing capacity under salt stress.…”
Section: Osmotic Stressmentioning
confidence: 99%
“…Cylindrical ionization chambers are the instruments of choice for use in photon calibration and dosimetry [1]. For each ionization chamber, correction factors are defined as quantities that are not the subjects of measurement, but still affect the measurement.…”
Section: Introductionmentioning
confidence: 99%